2018
DOI: 10.1186/s12913-018-3027-8
|View full text |Cite
|
Sign up to set email alerts
|

NHS health checks: a cross- sectional observational study on equity of uptake and outcomes

Abstract: BackgroundThe National Health Checks programme aims to reduce the incidence of cardiovascular diseases and health inequalities in England. We assessed equity of uptake and outcomes from NHS Health Checks in general practices in Bristol, UK.MethodsA cross-sectional study using patient-level data, from 38 general practices. We descriptively analysed the socioeconomic status (SES) of patients invited and the SES and ethnicity of those attending. Logistic regression was used to test associations between invitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 29 publications
5
31
1
Order By: Relevance
“…The nine included studies were conducted between 2011 and 2016, using data from 2008 to 2014. The sample sizes varied from 1380 patients [19] to 40,112 patients [20], and included between four [19,21] and 38 GP Practices [22]. The length of studies (including the follow up period) varied from 6 months [23] to 4 years [22].…”
Section: Study Characteristics and Methodological Qualitymentioning
confidence: 99%
“…The nine included studies were conducted between 2011 and 2016, using data from 2008 to 2014. The sample sizes varied from 1380 patients [19] to 40,112 patients [20], and included between four [19,21] and 38 GP Practices [22]. The length of studies (including the follow up period) varied from 6 months [23] to 4 years [22].…”
Section: Study Characteristics and Methodological Qualitymentioning
confidence: 99%
“…Our linked qualitative evaluation with staff delivering the telephone outreach intervention found that “matching” was important—to capitalize on outreach workers’ specialist skills and maximize the potential impact of the intervention. However, such matching could be difficult to achieve due to (a) ethnicity being poorly recorded in medical records, and (b) the support of participating primary care practices being required for outreach callers to be provided with appropriate lists of patients (T. J. Stone, E. Brangan, A. Chappell, V. Harrison, J. Horwood, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence on uptake in different ethnic groups was mixed, with conflicting findings . Analyses were limited by high levels of missing ethnicity data in primary care practice records, with uptake significantly lower for those with this data missing . Qualitative research with staff delivering health checks found perceptions that people from black and minority ethnic groups were less likely to attend, with language and cultural issues seen as major barriers …”
Section: Introductionmentioning
confidence: 99%
“…healthcheck.nhs.uk), which is a 5-yearly free check-up available for adults in the UK aged 40-74 years. However, only 43% of those invited for an NHS Health Check are reported to attend, 39 and it is likely that many non-attenders will be those most at risk. 40 OxRen provides an estimate of undiagnosed CKD in the UK population aged ≥60 years, including screen-detected rates, and will provide future estimates of incidence.…”
Section: Ethical Approvalmentioning
confidence: 99%